IMPLEMENTASI STRATEGI PENERAPAN KARTU TANDA PENDUDUK ELEKTRONIK (e-KTP) DI KABUPATEN MAMASA - Barnesi Datumongan; Martinus Sudi (MITZAL (Demokrasi, Komunikasi dan Budaya) : Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2020)
This study aims to determine the implementation of the strategy for implementing Electronic Identity Cards (e-KTP) in Mamasa Regency and the efforts made in implementing Electronic Identity Cards (e-KTP) in Mamasa Regency. This research used qualitative methods and the type of data collection used document review, interviews and observation. The results of the study show that the standard procedures for implementing Electronic KTP 2011 are through strategic programs in the form of organizational structures on behalf of regency and sub-district working groups, socialization, program implementers (HR), provision of facilities and infrastructure and population mobilization. Of these activities 44.30% have been realized with various obstacles, including slow distribution of equipment from the center and only one functioning, damaged equipment, and inaccessibility of some residents due to delays in mobile registration which are expected to be an alternative.